Estudo morfométrico dos crânios do acervo do laboratório de anatomia humana da Universidade Federal de Uberlândia - Calábria, Kenia Cristina (2020)
This research aimed to study the morphological characteristics of the skulls belonging to the collection of the Human Anatomy Laboratory (DEPAH) of the Biomedical Sciences Institute of the Federal University of Uberlândia. Thus, forming a database for future research. After being washed with neutral detergent and bleached in an aqueous solution of hydrogen peroxide, the 153 skulls were dried at room temperature and an evaluation of the material was carried out, including all those that had the craniometric points intact for further measurements. Cranioscopy was performed to check sex and then craniometry to determine ancestry. Through cranioscopy, 122 (79.74%) male skulls and 31 (20.26%) female skulls were detected. The calculation of the Horizontal Cephalic Index (ICH) allowed the classification of the skulls in dolichocephalus, subdolicocephalus, mesaticcephalus, subbrachycephalus and brachycephalus, the majority being brachycephalus, indicating a mongolian ancestry, both in male (47.06%) and in female (13.73%). According to the Vertical Index (IV.Pe), the skulls in platicephalus, mesocephalus and hipsicephalus were discriminated. Most of the male (39.22%) and female (9.81%) material consisted of mesocephalus skulls, determining a Caucasoid ancestry. The Transverse Index (IV.Po) was verified and the skulls were differentiated in stenocephalus, metriocephalus and tapinocephalus, the latter being present in greater numbers in both males (38.56%) and females (13.73%), demonstrating black and caucasoid ancestry. When assessing the Nasal Index, leptorrhine, mesorhine and platyrrhine skulls were found. In both sexes, the number of platyrrhines was higher, with 47.71% referring to males and 12.42% to females, evidencing black ancestry. Given the vastness of the subject, we were able to make a contribution to the other areas, providing a database for future research.